Axisymmetric Free Vibration of Soft Electroactive Circular Plates under Biasing Fields

Abstract

Soft electroactive materials (SEAMs) with large elastic deformation capacity as well as excellent electromechanical coupling characteristic have attracted increasing attention in the fields of mechanics and related engineering disciplines. Based on the nonlinear theory of electroelasticity and its linearized version for incremental fields, we derive the state-space formulations for small-amplitude free vibrations of an SEAM circular plate under large pre-deformation due to static biasing fields. An exact three-dimensional solution is then obtained by adopting the finite Hankel transform for the plate with an elastic simple support at the circular boundary. The exact solution for an isotropic linear elastic circular plate can be obtained as a particular and degenerated case. The model of generalized neo-Hookean compressible material is considered in numerical simulations. It is found that the natural frequency, while depending on the intrinsic parameters of the plate (e.g., initial thickness and electromechanical coupling coefficients), can be controlled effectively by the extrinsic factors (e.g., pre-stretch and biasing electric displacement). Results further indicate that Euler’s instability will occur under a certain combination of the biasing electric displacement and pre-stretch, which should be of practical importance when one intends to tune the dynamic characteristics of a plate by means of external loading.

This is a preview of subscription content, access via your institution.

Fig. 1
Fig. 2
Fig. 3
Fig. 4
Fig. 5
Fig. 6
Fig. 7
Fig. 8
Fig. 9
Fig. 10

References

  1. 1.

    O’Halloran A, O’Malley F, McHugh P. A review on dielectric elastomer actuators, technology, applications, and challenges. J Appl Phys. 2008;104(7):071101.

    Article  Google Scholar 

  2. 2.

    Pelrine R, Kornbluh R, Pei QB, Joseph J. High-speed electrically actuated elastomers with strain greater than 100%. Science. 2000;287(5454):836–9.

    Article  Google Scholar 

  3. 3.

    Sugimoto T, Ando A, Ono K, Morita Y, Hosoda K, Ishii D, Nakamura K. A lightweight push-pull acoustic transducer composed of a pair of dielectric elastomer films. J Acoust Soc Am. 2013;134(5):EL432–7.

    Article  Google Scholar 

  4. 4.

    Hosoya N, Baba S, Maeda S. Hemispherical breathing mode speaker using a dielectric elastomer actuator. J Acoust Soc Am. 2015;138(4):EL424–8.

    Article  Google Scholar 

  5. 5.

    Cao XN, Zhang MQ, Zhang Z, Xu Y, Xiao YH, Li TF. Review of soft linear actuator and the design of a dielectric elastomer linear actuator. Acta Mech Solida Sin. 2019;32(5):566–79.

    Article  Google Scholar 

  6. 6.

    Dorfmann A, Ogden RW. Nonlinear electroelasticity. Acta Mech. 2005;174(3–4):167–83.

    Article  Google Scholar 

  7. 7.

    Dorfmann L, Ogden RW. Nonlinear theory of electroelastic and magnetoelastic interactions. New York: Springer; 2014.

    Google Scholar 

  8. 8.

    Dorfman A, Ogden RW. Nonlinear electroelastostatics: incremental equations and stability. Int J Eng Sci. 2010;48(1):1–14.

    MathSciNet  Article  Google Scholar 

  9. 9.

    Wu B, Zhang CL, Zhang CZ, Chen WQ. Theory of electroelasticity accounting for biasing fields: retrospect, comparison and perspective. Adv Mech. 2016;46:201601 in Chinese.

    Google Scholar 

  10. 10.

    Suo ZG. Theory of dielectric elastomers. Acta Mech Solida Sin. 2010;23(6):549–78.

    Article  Google Scholar 

  11. 11.

    Dorfmann L. Ogden RW Nonlinear electroelasticity: material properties, continuum theory and applications. Proc R Soc A. 2017;473(2204):20170311.

    MathSciNet  Article  Google Scholar 

  12. 12.

    Dorfmann A, Ogden RW. Electroelastic waves in a finitely deformed electroactive material. IMA J Appl Math. 2010;75(4):603–36.

    MathSciNet  Article  Google Scholar 

  13. 13.

    Chen WQ, Dai HH. Waves in pre-stretched incompressible soft electro active cylinders: exact solution. Acta Mech Solida Sin. 2012;25(5):530–41.

    Article  Google Scholar 

  14. 14.

    Su YP, Wang HM, Zhang CL, Chen WQ. Propagation of non-axisymmetric waves in an infinite soft electroactive hollow cylinder under uniform biasing fields. Int J Solids Struct. 2016;81:262–73.

    Article  Google Scholar 

  15. 15.

    Wu B, Su YP, Chen WQ, Zhang CZ. On guided circumferential waves in soft electroactive tubes under radially inhomogeneous biasing fields. J Mech Phys Solids. 2017;99:116–45.

    MathSciNet  Article  Google Scholar 

  16. 16.

    Wang YZ, Li ZY, Chen WQ, Zhang CZ, Zhu J. Free vibration and active control of pre-stretched multilayered electroactive plates. Int J Solids Struct. 2019;180–181:108–24.

    Article  Google Scholar 

  17. 17.

    Mao RW, Wu B, Carrera E, Chen WQ. Electrostatically tunable small-amplitude free vibrations of pressurized electro-active spherical balloons. Int J Nonlinear Mech. 2019;117:103237.

    Article  Google Scholar 

  18. 18.

    Zhu FZ, Wu B, Destrade M, Chen WQ. Electrostatically tunable axisymmetric vibrations of soft electro-active tubes. J Sound Vib. 2020;483:115467.

    Article  Google Scholar 

  19. 19.

    Ding HJ, Xu RQ, Chi YW, Chen WQ. Free axisymmetric vibration of transversely isotropic piezoelectric circular plates. Int J Solids Struct. 1999;36(3):4629–52.

    MATH  Google Scholar 

  20. 20.

    Scheidler JJ, Asnani VM, Dapino MJ. Dynamically tuned magnetostrictive spring with electrically controlled stiffness. Smart Mater Struct. 2016;25:035007.

    Article  Google Scholar 

  21. 21.

    Wang YZ, Li XY, Chen WQ. Free vibration analysis of pre-stretched plates with electromechanical coupling. In: Symposium on piezoelectricity, acoustic waves, and device applications. 2013; https://doi.org/10.1109/SPAWDA.2013.6841141.

  22. 22.

    Zhao XH, Suo ZG. Method to analyze electromechanical stability of dielectric elastomers. Appl Phys Lett. 2007;91:061921.

    Article  Google Scholar 

  23. 23.

    Reddy JN. Theory and analysis of elastic plates and shells. 2nd ed. Milton Park: Taylor & Francis Group; 2007.

    Google Scholar 

  24. 24.

    Shmuel G, Pernas-Salomón R. Manipulating motions of elastomer films by electrostatically-controlled aperiodicity. Smart Mater Struct. 2016;25(12):125012.

    Article  Google Scholar 

  25. 25.

    https://3m.citrination.com/pif/000344?locale=en-US.

  26. 26.

    Liu LW, Liu YJ, Leng JS, Lau KT. Electromechanical stability of compressible dielectric elastomer actuators. Smart Mater Struct. 2011;20:115015.

    Article  Google Scholar 

  27. 27.

    Su YP, Broderick HC, Chen WQ, Destrade M. Wrinkles in soft dielectric plates. J Mech Phys Solids. 2018;119:298–318.

    MathSciNet  Article  Google Scholar 

  28. 28.

    Su YP, Wu B, Chen WQ, Destrade M. Finite bending and pattern evolution of the associated instability for a dielectric elastomer slab. Int J Solids Struct. 2019;158:191–209.

    Article  Google Scholar 

  29. 29.

    Bertoldi K, Gei M. Instability in multilayered soft dielectrics. J Mech Phys Solids. 2011;59(1):18–42.

    MathSciNet  Article  Google Scholar 

  30. 30.

    Dorfmann L, Ogden RW. Instabilities of an electroelastic plate. Int J Eng Sci. 2014;77:79–101.

    MathSciNet  Article  Google Scholar 

  31. 31.

    Zhao ZH, Shuai CG, Gao Y, Rustighi E, Xuan Y. An application review of dielectric electroactive polymer actuators in acoustics and vibration control. J Phys Conf Ser. 2016;744:012162.

    Article  Google Scholar 

  32. 32.

    Bortot E, Shmuel G. Tuning sound with soft dielectrics. Smart Mater Struct. 2017;26(4):045028.

    Article  Google Scholar 

  33. 33.

    Ding HJ, Xu RQ, Chen WQ, Chi YW. Free axisymmetric vibration of transversely isotropic laminated circular plates. Acta Mech Solida Sin. 1998;11(3):209–15.

    Google Scholar 

Download references

Acknowledgements

This work was supported by the National Natural Science Foundation of China (Nos. 11872329 and 11621062).

Author information

Affiliations

Authors

Corresponding author

Correspondence to Weiqiu Chen.

Appendices

Appendix A: Effective Electroelastic Moduli

The nonzero coefficients appearing in Eq. (12) under a biasing field in Fig. 1 are given by [12]:

$$\begin{aligned} \mathscr {A}_{01111}= & {} \frac{{2}}{\lambda _{{3}} }\{\varOmega _{{1}} \text{+ }\varOmega _{{3}} \lambda _{{1}}^{{2}} \lambda _{{3}}^{{2}} +[\lambda _{{1}}^{{2}} (2\varOmega _{{11}} \text{+ }\varOmega _{{2}} )+4\varOmega _{{12}} \lambda _{{1}}^{{2}} \text{+2 }\varOmega _{{22}} \lambda _{{1}}^{{4}} ]\text{+ }\varOmega _{{2}} \lambda _{{3}}^{{2}}\nonumber \\&{+2}\lambda _{{1}}^{{2}} \lambda _{{3}}^{{2}} [2\varOmega _{{12}} \text{+2 }\left( {\varOmega _{{13}} {+}\varOmega _{{22}} } \right) \lambda _{{1}}^{{2}} +{2}\varOmega _{{23}} \lambda _{{1}}^{{4}} \text{+ }\varOmega _{{22}} \lambda _{{3}}^{{2}} \text{+2 }\varOmega _{{23}} \lambda _{{1}}^{{2}} \lambda _{{3}}^{{2}} \text{+ }\varOmega _{{33}} \lambda _{{1}}^{{4}} \lambda _{{3}}^{{2}}]\} \end{aligned}$$
(A.1)
$$\begin{aligned} \mathscr {A}_{01122}= & {} \frac{{2}\lambda _{{1}}^{{2}}}{\lambda _{{3}} }[2\varOmega _{{11}} \text{+2 }\varOmega _{{2}} +4\varOmega _{{12}} \lambda _{{1}}^{{2}} +2\varOmega _{{22}} \lambda _{{1}}^{{4}} +({4}\varOmega _{{12}} +{2}\varOmega _{3} )\lambda _{{3}}^{{2}} \nonumber \\&+2\varOmega _{{22}} \lambda _{3}^{{4}} +2\lambda _{{1}}^{{2}} \lambda _{{3}}^{{2}} (2\varOmega _{{13}} +2\varOmega _{{22}} +{2}\varOmega _{{23}} \lambda _{{1}}^{{2}} +{2}\varOmega _{{23}} \lambda _{{3}}^{{2}} +\varOmega _{{33}} \lambda _{{1}}^{2} \lambda _{{3}}^{{2}} )] \end{aligned}$$
(A.2)
$$\begin{aligned} \mathscr {A}_{01133}= & {} {2}\lambda _{{3}} [2\varOmega _{{11}} \text{+2 }\varOmega _{{2}} +(6\varOmega _{12} +2\varOmega _{{3}} )\lambda _{{1}}^{{2}} +2(\varOmega _{{13}} +2\varOmega _{{22}} )\lambda _{{1}}^{{4}} +2\varOmega _{{23}} \lambda _{{1}}^{6} \nonumber \\&+2\varOmega _{{12}} \lambda _{{3}}^{{2}} +2(\varOmega _{{13}} +2\varOmega _{{22}} )\lambda _{{1}}^{{2}} \lambda _{{3}}^{{2}}+6\varOmega _{{23}} \lambda _{{1}}^{{4}} \lambda _{{3}}^{{2}} +2\varOmega _{{33}} \lambda _{{1}}^{6} \lambda _{{3}}^{{2}}] \nonumber \\&+\frac{4D_{3}^{2} }{\lambda _{{1}}^{{2}} \lambda _{3} }\{\lambda _{1}^{8} \lambda _{3}^{4} (\varOmega _{35} +2\varOmega _{36} \lambda _{{3}}^{{2}} )+\lambda _{{1}}^{6} \lambda _{{3}}^{{2}} [\varOmega _{{15}} +2\varOmega _{{16}} \lambda _{{3}}^{{2}} \nonumber \\&+(\varOmega _{{25}} +2\varOmega _{{26}} \lambda _{{3}}^{{2}} )(\lambda _{{1}}^{{2}} +\lambda _{{3}}^{{2}} )]\} \end{aligned}$$
(A.3)
$$\begin{aligned} \mathscr {A}_{03333}= & {} \frac{2\lambda _{{3}} }{\lambda _{{1}}^{{2}} }\{\varOmega _{1} +2\varOmega _{2} \lambda _{{1}}^{{2}} +\varOmega _{3} \lambda _{1}^{4} +2\lambda _{3}^{{2}} [\varOmega _{{11}} +4\varOmega _{12} \lambda _{{1}}^{{2}} +\lambda _{{1}}^{{4}} (2\varOmega _{{13}} +4\varOmega _{{22}} \nonumber \\&+4\varOmega _{{23}} \lambda _{{1}}^{2} +\varOmega _{{33}} \lambda _{{1}}^{4} )]\}+\frac{2D_{3}^{2} }{\lambda _{{1}}^{{2}} \lambda _{3} }\{4\varOmega _{35} \lambda _{1}^{8} \lambda _{3}^{4} +\lambda _{3}^{{2}} [8\varOmega _{36} \lambda _{1}^{8} \lambda _{3}^{4} +\varOmega _{5} \lambda _{{1}}^{{4}} \nonumber \\&+2\lambda _{{1}}^{{4}} \lambda _{{3}}^{{2}} (2\varOmega _{{15}} +3\varOmega _{6} +4\varOmega _{{25}} \lambda _{{1}}^{2} +4\varOmega _{16} \lambda _{3}^{2} +8\varOmega _{26} \lambda _{{1}}^{{2}} \lambda _{3}^{{2}} )]\} \nonumber \\&+4D_{3}^{4} \lambda _{{1}}^{6} \lambda _{3}^{3} [\varOmega _{55} +4\lambda _{{3}}^{{2}} (\varOmega _{56} +\varOmega _{66} \lambda _{{3}}^{{2}} )] \end{aligned}$$
(A.4)
$$\begin{aligned} \mathscr {A}_{01212}= & {} \frac{2}{\lambda _{3} }(\varOmega _{1} +\varOmega _{2} \lambda _{3}^{{2}} ),{\, \, }\mathscr {A}_{01221} =-\frac{2\lambda _{{1}}^{{2}} }{\lambda _{3} }(\varOmega _{2} +\varOmega _{3} \lambda _{3}^{{2}} ) \end{aligned}$$
(A.5)
$$\begin{aligned} \mathscr {A}_{01313}= & {} \frac{2}{\lambda _{3} }(\varOmega _{1} +\varOmega _{2} \lambda _{1}^{{2}} +D_{3}^{2} \varOmega _{6} \lambda _{1}^{4} \lambda _{3}^{{2}} ),{\, \, }\mathscr {A}_{01331} =-2\lambda _{3} (\varOmega _{2} +\varOmega _{3} \lambda _{1}^{{2}} -D_{3}^{2} \varOmega _{6} \lambda _{{1}}^{{4}} ) \end{aligned}$$
(A.6)
$$\begin{aligned} \mathscr {A}_{03131}= & {} \frac{2\lambda _{{3}} }{\lambda _{{1}}^{{2}} }\{\varOmega _{1} +\varOmega _{2} \lambda _{1}^{{2}} +D_{3}^{2} \lambda _{1}^{4} [\varOmega _{5} +\varOmega _{6} (\lambda _{{1}}^{{2}} +2\lambda _{3}^{{2}} )]\} \end{aligned}$$
(A.7)
$$\begin{aligned} \varvec{\varGamma }_{01\text{13 }}= & {} \frac{{4}D_{3} \lambda _{1}^{{4}} }{\lambda _{{3}} }\{\varOmega _{{14}} +\varOmega _{{24}} (\lambda _{{1}}^{{2}} +\lambda _{3}^{{2}} )\text{+ }\lambda _{{3}}^{{2}} [\varOmega _{15} +\varOmega _{34} \lambda _{{1}}^{{2}} +\varOmega _{16} \lambda _{{3}}^{{2}} +(\varOmega _{26} +\varOmega _{35} )\lambda _{{1}}^{{2}} \lambda _{3}^{{2}}\nonumber \\&+\varOmega _{26}\lambda _{3}^{4} +\varOmega _{36} \lambda _{{1}}^{{2}} \lambda _{3}^{4} +\varOmega _{25} (\lambda _{{1}}^{{2}} +\lambda _{3}^{{2}} )]\} \end{aligned}$$
(A.8)
$$\begin{aligned} \varvec{\varGamma }_{0131}= & {} 2D_{3} \lambda _{1}^{{2}} \lambda _{{3}} [\varOmega _{5} +\varOmega _{6} (\lambda _{{1}}^{{2}} +\lambda _{3}^{{2}} )] \end{aligned}$$
(A.9)
$$\begin{aligned} \varvec{\varGamma }_{0333}= & {} 4D_{3} \lambda _{1}^{{2}} \lambda _{{3}} \{\varOmega _{14} +\varOmega _{5} +2\varOmega _{24} \lambda _{1}^{{2}} +\varOmega _{34} \lambda _{1}^{4} +(\varOmega _{15} +2\varOmega _{6} )\lambda _{3}^{{2}} +\varOmega _{16} \lambda _{3}^{4} \nonumber \\&+\lambda _{1}^{2}\lambda _{3}^{{2}} (2\varOmega _{25} +2\varOmega _{26} \lambda _{3}^{{2}} +\varOmega _{35} \lambda _{1}^{2} +\varOmega _{36} \lambda _{1}^{2} \lambda _{3}^{2} )+D_{3}^{2} \lambda _{1}^{4} [\varOmega _{45} \nonumber \\&+(2\varOmega _{46}+\varOmega _{55} )\lambda _{3}^{{2}} +3\varOmega _{56} \lambda _{3}^{4} +2\varOmega _{66} \lambda _{3}^{6} ]\} \end{aligned}$$
(A.10)
$$\begin{aligned} K_{011}= & {} 2\lambda _{{3}} (\varOmega _{4} +\varOmega _{5} \lambda _{1}^{2} +\varOmega _{6} \lambda _{1}^{2} ) \end{aligned}$$
(A.11)
$$\begin{aligned} K_{033}= & {} \frac{2\lambda _{1}^{2} }{\lambda _{{3}} }\{\varOmega _{4} +\lambda _{3}^{2} (\varOmega _{5} +\varOmega _{6} \lambda _{3}^{2} )+2D_{3}^{2} \lambda _{{1}}^{4} [\varOmega _{44} +2\varOmega _{45} \lambda _{3}^{{2}}\nonumber \\&+\lambda _{3}^{4} (2\varOmega _{46} +\varOmega _{55} +2\varOmega _{56} \lambda _{3}^{{2}} +\varOmega _{66} \lambda _{3}^{4} )]\} \end{aligned}$$
(A.12)

In addition, the following relation holds

$$\begin{aligned} \mathscr {A}_{01111} -\mathscr {A}_{01122} =\mathscr {A}_{01221} +\mathscr {A}_{01212} \end{aligned}$$
(A.13)

If adopting the generalized neo-Hookean model given in Eq. (48), the expressions for the corresponding effective electroelastic moduli are given by:

$$\begin{aligned} c_{11}= & {} K\lambda _{{1}}^{2} \lambda _{3} +\frac{7}{9}\mu \lambda _{{1}}^{{-4/3}} \lambda _{{3}}^{{-5/3}} +\frac{5}{9}\mu \lambda _{{1}}^{{-10/3}} \lambda _{{3}}^{{1/3}}\nonumber \\ c_{12}= & {} -\frac{D_{3}^{2} }{\varepsilon _{0} \lambda _{3}^{2} }\left( {\gamma _{1} +\lambda _{3}^{2} \gamma _{2} } \right) +K\left( {2\lambda _{1}^{2} \lambda _{3} -1} \right) +\frac{2}{9}\mu \lambda _{{1}}^{{-10/3}} \lambda _{{3}}^{{-5/3}} \left( {-4\lambda _{1}^{2} +\lambda _{3}^{2} } \right) \nonumber \\ c_{13}= & {} \frac{D_{3}^{2} \left( {-\gamma _{1} +\gamma _{2} \lambda _{3}^{2} } \right) }{\varepsilon _{0} \lambda _{3}^{2} }+K\left( {2\lambda _{1}^{2} \lambda _{3} -1} \right) -\frac{2}{9}\mu \lambda _{{1}}^{{-10/3}} \lambda _{{3}}^{{-5/3}} \left( {\lambda _{1}^{2} +2\lambda _{3}^{2} } \right) \nonumber \\ c_{33}= & {} -\frac{2D_{3}^{2} \gamma _{2} \left( {-3\gamma _{1} +\gamma _{2} \lambda _{3}^{2} } \right) }{\varepsilon _{0} \left( {\gamma _{1} +\gamma _{2} \lambda _{3}^{2} } \right) }+K\lambda _{1}^{2} \lambda _{3} +\frac{2}{9}\mu \lambda _{{1}}^{\mathrm{-10/3}} \lambda _{{3}}^{\mathrm{-5/3}} \left( {5\lambda _{1}^{2} +\lambda _{3}^{2} } \right) \nonumber \\ c_{58}= & {} -K\left( {\lambda _{1}^{2} \lambda _{3} -1} \right) +\frac{1}{3}\mu \lambda _{{1}}^{\mathrm{-10/3}} \lambda _{{3}}^{\mathrm{-5/3}} \left( {2\lambda _{1}^{2} +\lambda _{3}^{2} } \right) \nonumber \\&+\frac{D_{3}^{2} }{\varepsilon _{0} \left( {\gamma _{1} +\gamma _{2} \lambda _{1}^{2} } \right) \lambda _{3}^{2} }\left[ {\gamma _{1}^{2} -\gamma _{2}^{2} \lambda _{1}^{2} \lambda _{3}^{2} +\gamma _{1} \gamma _{2} \left( {\lambda _{1}^{2} +\lambda _{3}^{2} } \right) } \right] \nonumber \\ c_{55}= & {} -\frac{2D_{3}^{2} \gamma _{2}^{2} \lambda _{1}^{2} }{\varepsilon _{0} \left( {\gamma _{1} +\gamma _{2} \lambda _{1}^{2} } \right) }+\mu \lambda _{{1}}^{\mathrm{-4/3}} \lambda _{{3}}^{\mathrm{-5/3}} ,\quad c_{88} =\frac{2D_{3}^{2} \gamma _{1} \gamma _{2} }{\varepsilon _{0} \left( {\gamma _{1} +\gamma _{2} \lambda _{1}^{2} } \right) }+\mu \lambda _{{1}}^{\mathrm{-10/3}} \lambda _{{3}}^{\mathrm{1/3}} \nonumber \\ e_{15}= & {} -\frac{D_{3} \gamma _{2} \lambda _{1}^{2} }{\gamma _{1} +\gamma _{2} \lambda _{1}^{2} },\quad e_{31} =D_{3} , \quad e_{33} =-\frac{2D_{3} \gamma _{2} \lambda _{3}^{2} }{\gamma _{1} +\gamma _{2} \lambda _{3}^{2}}+D_{3} ,\nonumber \\ \varepsilon _{11}= & {} \frac{\varepsilon _{0} \lambda _{1}^{2} }{2(\gamma _{1} +\gamma _{2} \lambda _{1}^{2} )},\quad \varepsilon _{33} =\frac{\varepsilon _{0} \lambda _{3}^{2} }{2(\gamma _{1} +\gamma _{2} \lambda _{3}^{2} )} \end{aligned}$$
(A.14)

Appendix B: Coefficients in Eqs. (19), (20), (21), (25) and (26)

The coefficients in Eqs. (19), (20) and (21) are given by:

$$\begin{aligned} \beta _{1}= & {} 1/c_{88} , \quad \beta _{2} =c_{58} \beta _{1} , \quad \beta _{3} =e_{15} \beta _{1} , \quad \beta _{4} =\beta _{1} (c_{58} -c_{88} )+1 \end{aligned}$$
(B.1)
$$\begin{aligned} \beta _{5}= & {} \beta _{2} (c_{58} -c_{88} )-\left( {c_{55} -c_{58} } \right) , \quad \beta _{6} =\beta _{3} \left( {c_{58} -c_{88} } \right) , \quad \beta _{7} =e_{15} \beta _{1}\end{aligned}$$
(B.2)
$$\begin{aligned} \beta _{8}= & {} e_{15} \left( {\beta _{2} -1} \right) , \quad \beta _{9} =e_{15} \beta _{3} +\varepsilon _{11} , \quad \beta _{10} =\frac{e_{31} e_{33} +c_{13} \varepsilon _{33} }{e_{33}^{2}+c_{33} \varepsilon _{33} }\end{aligned}$$
(B.3)
$$\begin{aligned} \beta _{11}= & {} \frac{\varepsilon _{33} }{e_{33}^{2}+c_{33} \varepsilon _{33}},\quad \beta _{12} =\frac{e_{33} }{e_{33}^{2}+c_{33} \varepsilon _{33} }, \quad \beta _{13} =\frac{c_{13} e_{33} -c_{33} e_{31} }{e_{33}^{2}+c_{33} \varepsilon _{33} }\end{aligned}$$
(B.4)
$$\begin{aligned} \beta _{14}= & {} \frac{c_{33} }{e_{33}^{2}+c_{33} \varepsilon _{33} }, \quad \beta _{15} =-c_{11} +c_{13} \beta _{10} +e_{31} \beta _{13} , \quad \beta _{16} =c_{13} \beta _{11} +e_{31} \beta _{12}\end{aligned}$$
(B.5)
$$\begin{aligned} \beta _{17}= & {} c_{13} \beta _{12} -e_{31} \beta _{14} , \quad \beta _{18} =c_{11} -c_{13} \beta _{10} -e_{31} \beta _{13} , \quad \beta _{19} =c_{12} -c_{13} \beta _{10} -e_{31} \beta _{13} \end{aligned}$$
(B.6)
$$\begin{aligned} \beta _{20}= & {} 1/\beta _{4} , \quad \beta _{21} =\left( {c_{55} -c_{58} } \right) -\beta _{2} (c_{58} -c_{88} ), \quad \beta _{22} =(c_{58} -c_{88} )\beta _{3} \end{aligned}$$
(B.7)

In Eqs. (25) and (26), the coefficients are given by:

$$\begin{aligned} f_{1}= & {} c_{11} \beta _{1}, \quad f_{2} =t_{c} \beta _{2}, \quad f_{3} =t_{c} \beta _{3} \sqrt{\frac{c_{11} }{\varepsilon _{33} }}, \quad f_{4} =t_{c} \beta _{4} , \quad f_{5} =\frac{t_{c}^{2} \beta _{5} }{c_{11} } \end{aligned}$$
(B.8)
$$\begin{aligned} f_{6}= & {} \frac{t_{c}^{2} \beta _{6} }{\sqrt{c_{11} \varepsilon _{33}}}, \quad f_{7} =t_{c}^{2} \beta _{7} \sqrt{\frac{c_{11} }{\varepsilon _{33} }}, \quad f_{8} =\frac{t_{c}^{2} \beta _{8} }{\sqrt{c_{11} \varepsilon _{33}}} \quad f_{9} =\frac{t_{c}^{2} \beta _{9} }{\varepsilon _{33}} \end{aligned}$$
(B.9)
$$\begin{aligned} f_{10}= & {} \frac{t_{c}^{2} \beta _{15} }{c_{11}}, \quad f_{11} =t_{c} \beta _{16}, \quad f_{12} =t_{c} \beta _{17} \sqrt{\frac{\varepsilon _{33} }{c_{11}}}, \quad f_{13} =t_{c} \beta _{10} \end{aligned}$$
(B.10)
$$\begin{aligned} f_{14}= & {} c_{11} \beta _{11}, \quad f_{15} =\sqrt{c_{11} \varepsilon _{33} } \beta _{12}, \quad f_{16} =t_{c} \beta _{13} \sqrt{\frac{\varepsilon _{33} }{c_{11}}}, \quad f_{17} =\beta _{14} \varepsilon _{33} \end{aligned}$$
(B.11)

Appendix C: Free Vibration of an Isotropic Linear Elastic Circular Plate

Substituting \(D_{3} =0\) and \(\lambda _{1} =\lambda _{3} =1\) into Eq. (A.14) gives

$$\begin{aligned} \begin{array}{l} c_{11} =c_{33} =K+\frac{4}{3}\mu ,\quad c_{12} =c_{13} =K-\frac{2}{3}\mu ,\quad c_{58} =c_{55} =c_{88} =\mu , \\ e_{15} =e_{31} =e_{33} =0,\quad \varepsilon _{11} =\varepsilon _{33} =\varepsilon _{0} \\ \end{array} \end{aligned}$$
(C.1)

The material then becomes isotropic and linear elastic. In fact, Eq. (38) is accordingly decoupled into two equations under the same boundary conditions:

$$\begin{aligned} \frac{\text{ d }{\varvec{R}}_{1}}{\text{ d }\zeta }= & {} {\varvec{M}}^{*}{\varvec{R}}_{1} \end{aligned}$$
(C.2)
$$\begin{aligned} \frac{\text{ d }{\varvec{R}}_{2}}{\text{ d }\zeta }= & {} {\varvec{M}}^{**}{\varvec{R}}_{2} \end{aligned}$$
(C.3)

where

$$\begin{aligned} {\varvec{R}}_{1}= & {} \left[ {{\begin{array}{*{20}c} {U\left( \zeta \right) } &{}\quad {\sigma \left( \zeta \right) } &{}\quad {\tau \left( \zeta \right) } &{}\quad {W\left( \zeta \right) } \\ \end{array} }} \right] ^{\mathrm{T}},\quad {\varvec{R}}_{2} =\left[ {{\begin{array}{*{20}c} {D\left( \zeta \right) } &{}\quad {\Phi \left( \zeta \right) } \\ \end{array} }} \right] ^{\mathrm{T}} \end{aligned}$$
(C.4)
$$\begin{aligned} {\varvec{M}}^{*}= & {} \left[ {{\begin{array}{*{20}c} 0 &{}\quad {{\varvec{M}}_{1}^{*} } \\ {{\varvec{M}}_{2}^{*} } &{}\quad 0 \\ \end{array} }} \right] ,\quad {\varvec{M}}^{**}=\left[ {{\begin{array}{*{20}c} 0 &{}\quad {-f_{9} k^{2}} \\ {-f_{17} } &{}\quad 0 \\ \end{array} }} \right] \end{aligned}$$
(C.5)
$$\begin{aligned} {\varvec{M}}_{1}^{*}= & {} \left[ {{\begin{array}{*{20}c} {f_{1} } &{}\quad {f_{2} k} \\ {-f_{4} k} &{}\quad {-f_{5} k^{2}-\frac{\rho \omega ^{2}h^{2}}{c_{11} }} \\ \end{array} }} \right] ,\quad {\varvec{M}}_{2}^{*} =\left[ {{\begin{array}{*{20}c} {-\frac{\rho \omega ^{2}h^{2}}{c_{11} }-f_{10} k^{{2}}} &{}\quad {f_{11} k} \\ {-f_{13} k} &{}\quad {f_{14} } \\ \end{array} }} \right] \end{aligned}$$
(C.6)

The solutions of Eqs. (C.2) and (C.3), respectively, are:

$$\begin{aligned} {\varvec{R}}_{k} \left( \zeta \right) ={\varvec{T}}_{k} \left( \zeta \right) {\varvec{R}}_{k} \left( 0 \right) \quad (k=1,2) \end{aligned}$$
(C.7)

where \({\varvec{T}}_{1} \left( \zeta \right) =e^{{\varvec{M}}^{*}\zeta }, \quad {\varvec{T}}_{2} \left( \zeta \right) =e^{{\varvec{M}}^{**}\zeta }\).

Setting \(\zeta ={1}\) in Eq. (C.7) gives:

$$\begin{aligned} {\varvec{R}}_{1} \left( 1 \right) ={\varvec{F}}^{*}{\varvec{R}}_{1} \left( 0 \right) \end{aligned}$$
(C.8)

where \({\varvec{F}}^{*}={\varvec{T}}_{1} \left( {{1}} \right) \).

The boundary conditions at the bottom and top surfaces of the plate are:

$$\begin{aligned} \dot{{T}}_{0zz} (h)=\dot{{T}}_{0rz} (h)=\dot{{T}}_{0zz} (0)=\dot{{T}}_{0rz} (0)=0 \end{aligned}$$
(C.9)

Substituting Eq. (C.9) into Eq. (C.8) gives:

$$\begin{aligned} \left[ {{\begin{array}{*{20}c} {F_{21}^{*} } &{}\quad {F_{24}^{*} } \\ {F_{31}^{*} } &{}\quad {F_{34}^{*} } \\ \end{array} }} \right] \left\{ {{\begin{array}{*{20}c} {U(0)} \\ {W(0)} \\ \end{array} }} \right\} =0 \end{aligned}$$
(C.10)

The determinant of the coefficient matrix must be zero for non-trivial solutions, giving rise to the corresponding characteristic equation. Then, the corresponding mode shape can also be obtained by the inverse Hankel transform. For more details, the reader can also refer to Ding et al. [33], which is for transversely isotropic laminated circular plates.

Appendix D: Vibration Mode Shapes

See Figs. 111213 and 14.

Fig. 11
figure11

The mode shape of an SEAM circular plate with \(\lambda _{{1}} =1.5\), \(\lambda _{{3}} =1\), \(D=0.1\), \(t_{0} =0.1\), \(\gamma _{1} =\gamma _{2} ={0.2}\) and the lowest dimensionless frequency \(\bar{{\omega }}=2.953\) (Dotted lines: initial mesh; Solid lines: mode shape)

Fig. 12
figure12

The mode shape of an SEAM circular plate with \(\lambda _{{1}} =1.5\), \(\lambda _{{3}} =1\), \(D=10\), \(t_{0} =0.1\), \(\gamma _{1} =\gamma _{2} ={0.2}\) and the lowest dimensionless frequency \(\bar{{\omega }}=2.22{2}\) (Dotted lines: initial mesh; Solid lines: mode shape)

Fig. 13
figure13

The mode shape of an SEAM circular plate with \(\lambda _{{1}} =1\), \(\lambda _{{3}} =2\), \(D=0.1\), \(t_{0} =0.1\), \(\gamma _{1} =\gamma _{2} ={0.2}\) and the lowest dimensionless frequency \(\bar{{\omega }}=2.598\) (Dotted lines: initial mesh; Solid lines: mode shape)

Fig. 14
figure14

The mode shape of an SEAM circular plate with \(\lambda _{{1}} =1\), \(\lambda _{{3}} =2\), \(D{=10}\), \(t_{0} =0.1\), \(\gamma _{1} =\gamma _{2} ={0.2}\) and the lowest dimensionless frequency \(\bar{{\omega }}=2.63{0}\) (Dotted lines: initial mesh; Solid lines: mode shape)

Appendix E: Euler’s Instability

This type of instability is common in daily life and engineering, which also attracts a lot of interest in the study of elastomeric structures. The static criterion of Euler instability is as follows. A small disturbance is first applied to the elastomer under a biasing field. If the disturbance satisfies the incremental governing equations and the incremental boundary conditions, Euler instability then occurs and the biasing field is the critical biasing field. The following gives the detailed analysis according to the above criterion of Euler instability.

The constitutive relations for the incremental field are given in Eq. (15). The equilibrium differential equations and electrostatic equation are

$$\begin{aligned} \begin{array}{l} \frac{\partial \dot{{T}}_{0rr} }{\partial r}+\frac{\dot{{T}}_{0rr} -\dot{{T}}_{0\theta \theta } }{r}+\frac{\partial \dot{{T}}_{0zr} }{\partial z}=0 \\ \frac{\partial \dot{{T}}_{0rz} }{\partial r}+\frac{\dot{{T}}_{0rz} }{r}+\frac{\partial \dot{{T}}_{0zz} }{\partial z}=0 \\ \frac{\partial \dot{{D}}_{l0r} }{\partial r}+\frac{\dot{{D}}_{l0r} }{r}+\frac{\partial \dot{{D}}_{l0z} }{\partial z}=0 \\ \end{array} \end{aligned}$$
(E.1)

which is obtained from Eq. (17) by simply discarding the inertia terms.

The state equation is still in the form of Eq. (18), where, however, all inertia terms should be discarded. As in Sect. 3.1, we can derive:

$$\begin{aligned} \frac{\text{ d }{\varvec{R}}(\zeta )}{\text{ d }\zeta }=\varvec{\bar{{M}}R}(\zeta ) \end{aligned}$$
(E.2)

where \(\varvec{\bar{{M}}}\) is the corresponding system matrix.

Under the three boundary conditions of Eqs. (41), (42) and (43), the characteristic equations for non-trivial solutions can be similarly obtained as:

$$\begin{aligned}&\left| {{\begin{array}{*{20}c} {\bar{{F}}_{21} } &{}\quad {\bar{{F}}_{25} } &{}\quad {\bar{{F}}_{26} } \\ {\bar{{F}}_{31} } &{}\quad {\bar{{F}}_{35} } &{}\quad {\bar{{F}}_{36} } \\ {\bar{{F}}_{41} } &{}\quad {\bar{{F}}_{45} } &{}\quad {\bar{{F}}_{46} } \\ \end{array} }} \right| =0 \end{aligned}$$
(E.3)
$$\begin{aligned}&\left| {{\begin{array}{*{20}c} {\bar{{F}}_{21} } &{}\quad {\bar{{F}}_{23} } &{}\quad {\bar{{F}}_{25} } \\ {\bar{{F}}_{41} } &{}\quad {\bar{{F}}_{43} } &{}\quad {\bar{{F}}_{45} } \\ {\bar{{F}}_{61} } &{}\quad {\bar{{F}}_{63} } &{}\quad {\bar{{F}}_{65} } \\ \end{array} }} \right| =0 \end{aligned}$$
(E.4)
$$\begin{aligned}&\left| {{\begin{array}{*{20}c} {\bar{{F}}_{21} } &{}\quad {\bar{{F}}_{23} } &{}\quad {\bar{{F}}_{25} } \\ {\bar{{F}}_{31} } &{}\quad {\bar{{F}}_{33} } &{}\quad {\bar{{F}}_{35} } \\ {\bar{{F}}_{41} } &{}\quad {\bar{{F}}_{43} } &{}\quad {\bar{{F}}_{45} } \\ \end{array} }} \right| =0 \end{aligned}$$
(E.5)

where \(\varvec{\bar{{F}}}=\text{ e}^{\varvec{\bar{{M}}}}\).

When Eqs. (E.3), (E.4) or (E.5) is satisfied, instability occurs. The results for the critical points in Figs. 5b and 7b can be all determined from these characteristic equations.

Rights and permissions

Reprints and Permissions

About this article

Verify currency and authenticity via CrossMark

Cite this article

Cao, Y., Zhu, J., Wu, B. et al. Axisymmetric Free Vibration of Soft Electroactive Circular Plates under Biasing Fields. Acta Mech. Solida Sin. (2021). https://doi.org/10.1007/s10338-020-00211-x

Download citation

Keywords

  • Soft electroactive materials
  • Circular plate
  • Free vibration
  • State-space method
  • Biasing fields